Declarative vs. operational in the orientation of the non-reimbursable financing programs of investments towards sustainability - Irina Manolescu; Stanislav Percic; Mihai Talmaciu (CES Working Papers, 2019)
Sustainability is one of the topics with undeniable relevance both in research and in global society. The objectives of the research aim to determine the proportions of the economic, social and environmental criteria within the project selection process, to segment the selected projects according to the sustainable approach dimensions and to highlight the sustainable and unsustainable investments made with European funds. The research methodology is mixed, quantitative and qualitative. For our research we have adapted an instrument developed by UNOPS, called Sustainability Marker, by using three of the four proposed major groups: social, environmental and economic. The results of the study support the main research hypothesis, namely an orientation towards sustainability at the programmatic level, but with relatively small proportions of the environmental and social objectives within the selection criteria, the implementation of the selected projects and the functioning of the investment objectives.
Keywords: 330; sustainability; project; project management